NOP58 induction potentiates chemoresistance of colorectal cancer cells through aerobic glycolysis as evidenced by proteomics analysis - Wang, Feifei; Yu, Bin; Yu, Quanyong; Wang, Guanglin; Li, Baokun; Guo, Ganlin; Wang, Handong; Shen, Hui; Li, Shujin; Ma, Chunling; Jia, Xianxian; Wang, Guiying; et al. (Frontiers in Pharmacology, 2023)
Introduction: The majority of individuals diagnosed with advanced colorectal cancer (CRC) will ultimately acquire resistance to 5-FU treatment. An increasing amount of evidence indicates that aerobic glycolysis performs a significant function in the progression and resistance of CRC. Nevertheless, the fundamental mechanisms remain to be fully understood. Methods: Proteomic analysis of 5-FU resistant CRC cells was implemented to identify and determine potential difference expression protein. Results: These proteins may exhibit resistance mechanisms that are potentially linked to the process of aerobic glycolysis. Herein, we found that nucleolar protein 58 (NOP58) has been overexpressed within two 5-FU resistant CRC cells, 116-5FuR and Lovo-5FuR. Meanwhile, the glycolysis rate of drug-resistant cancer cells has increased. NOP58 knockdown decreased glycolysis and enhanced the sensitivity of 116-5FuR and Lovo-5FuR cells to 5FU. Conclusion: The proteomic analysis of chemoresistance identifies a new target involved in the cellular adaption to 5-FU and therefore highlights a possible new therapeutic strategy to overcome this resistance.